Estimation of severe drug-drug interaction warnings by medical specialist groups for Austrian nationwide eMedication - Rinner, C.; Sauter, S. K.; Neuhofer, L. M.; Edlinger, D.; Grossmann, W.; Wolzt, M.; Endel, G.; Gall, W. (Applied Clinical Informatics, 2014)
Objective: The objective of this study is to estimate the amount of severe drug-drug interaction warnings per medical specialist group triggered by prescribed drugs of a patient before and after the introduction of a nationwide eMedication system in Austria planned for 2015.Methods: The estimations of interaction warnings are based on patients’ prescriptions of a single health care professional per patient, as well as all patients’ prescriptions from all visited health care professionals. We used a research database of the Main Association of Austrian Social Security Organizations that contains health claims data of the years 2006 and 2007.Results: The study cohort consists of about 1 million patients, with 26.4 million prescribed drugs from about 3,400 different health care professionals. The estimation of interaction warnings show a heterogeneous pattern of severe drug-drug-interaction warnings across medical specialist groups.Conclusion: During an eMedication implementation it must be taken into consideration that different medical specialist groups require customized support.Citation: Rinner C, Sauter SK, Neuhofer LM, Edlinger D, Grossmann W, Wolzt M, Endel G, Gall W. Estimation of severe drug-drug interaction warnings by medical specialist groups for Austrian nationwide eMedication. Appl Clin Inf 2014; 5: 603–611http://dx.doi.org/10.4338/ACI-04-RA-0030
Keywords: Drug interactions; medical informatics; public health informatics